Screening Auschwitz : Wanda Jakubowska’s the last stage and the politics of commemoration (2018)
This study, about the early screen representation of Auschwitz—the “capital of the Holocaust”1 —is a continuation of my previous research that resulted in the book Polish Film and the Holocaust: Politics and Memory, published in 2012.2 That book included a chapter on The Last Stage (1948, also known under the title The Last Stop, Ostatni etap), directed by Auschwitz survivor Wanda Jakubowska (1907–1998). The film’s cinematic, political, and ideological layers warrant a more detailed monograph. In The Last Stage, Jakubowska depicted the monstrosity of Konzentrationslager Auschwitz-Birkenau and drew on her own camp experiences to portray the factory of death. She made her film with the significant participation of other Auschwitz survivors, including the German communist Gerda Schneider, who coscripted the film. With its pioneering, powerful dramatization of the camp experience, The Last Stage established several quasi-documentary themes easily discernible in later Holocaust narratives: the dark, realistic images of the camp (the film was shot on location in Auschwitz-Birkenau); the passionate moral appeal; and the clear divisions between victims and victimizers. Jakubowska’s film shaped the future representation of Nazi German concentration camps. It also introduced the images of camp life that are now archetypal and notable in numerous films about the Holocaust and the “concentrationary universe” (l’univers concentrationnaire). These images include, among others, morning and evening roll calls on the Appelplatz; the arrival of a transport train at Auschwitz II (Vernichtungslager Birkenau)—a steam locomotive slowly moving, in a thick fog, through the “death gate” toward the armed SS guards with dogs; the separation of families upon their arrival at the Birkenau unloading ramp; the tracking shot over the belongings left by the gassed camp victims; shots of crowded prisoners’ barracks; and the juxtaposition of the camp orchestra playing